Gaze Mechanisms for Situated Interaction with Embodied Agents - Andrist, Sean (University of Wisconsin - Madison, 2016)
Computer interfaces represented as embodied agents, either virtually as animated characters or physically as humanlike robots, utilize a powerful metaphor of everyday social interaction in order to communicate effectively with human users. One of the most promising features of embodied agents is their ability to embody humanlike attributes and make use of nonverbal conversational cues just as people do. Gaze is a particularly important nonverbal signal in social interactions and is utilized in several rich communication mechanisms with which people are intuitively familiar.